Nitric oxide as a key component in hormone-regulated processes - Simontacchi, Marcela (2013)
Nitric oxide (NO) is a small gaseous molecule, with a free radical nature that allows it to participate in a wide spectrum of biologically important reactions. NO is an endogenous product in plants, where different biosynthetic pathways have been proposed. First known in animals as a signaling molecule in cardiovascular and nervous systems, it has turned up to be an essential component for a wide variety of hormone-regulated processes in plants. Adaptation of plants to a changing environment involves a panoply of processes, which include the control of CO2 fixation and water loss through stomatal closure, rearrangements of root architecture as well as growth restriction. The regulation of these processes requires the concerted action of several phytohormones, as well as the participation of the ubiquitous molecule NO. This review analyzes the role of NO in relation to the signaling pathways involved in stomatal movement, plant growth and senescence, in the frame of its interaction with abscisic acid, auxins, gibberellins, and ethylene.